Inhibitory effects of tanshinone IIA from Salvia miltiorrhiza Bge on human bladder cancer BIU-87 cells and xenograft in nude mice - HUANG,Tao (2020)
Abstract The objective of this study was to investigate the inhibitory effects of tanshinone IIA on human bladder cancer BIU-87 cells and the xenograft in nude mice. BIU-87 cells were treated with tanshinone IIA with concentration of 0.5, 1, 2 and 4 g/L. The cell proliferation, cycle and apoptosis were detected. The nude mice with BIU-87 cell xenograft were treated with normal saline (control), 5-fluorouracil (5-FU), 200, 400 and 600 mg/kg tanshinone IIA, respectively. The animal body weight and growth of tumor were measured. The expressions of B-cell lymphoma-2 (Bcl-2), Caspase-3 and proliferating cell nuclear antigen (PCNA) protein in xenograft were detected. The apoptosis index of cells was determined. Results showed that, tanshinone IIA inhibited the proliferation of BIU-87 cells, promoted their apoptosis, and arrested more cells in G0/G1 phase. Tanshinone IIA significantly inhibited the growth of xenograft in nude mice and promoted the apoptosis of tumor cells in xenograft. Tanshinone IIA down-regulated Bcl-2 and PCNA expression and up-regulated Caspase-3 expression in xenograft. In conclusion, tanshinone IIA has inhibitory effects on human bladder cancer BIU-87 cells, and can inhibit the BIU-87 cells xenograft in nude mice.